CHARACTERIZATION OF MATERNAL DEATHS IN THREE HEALTHCARE REGIONS OF THE CENTER-NORTH OF BAHIACARACTERIZAÇÃO - Vanessa Correia Coelho; Magna Santos Andrade; Chalana Duarte de Sena; Laura Emanuela Lima Costa; Isaiane Santos Bittencourt (Universidade Federal do Paraná, 2016)
ABSTRACT: The present study aimed to describe the epidemiological profile of maternal mortality in the cities that constitute the 15th, 16th and 28th Regional Health Boards - Bahia, occurred between 2006 and 2012.Cross-sectional study with secondary data from 113 maternal deaths recorded in the Mortality Information System, conducted from July to September 2013. Deaths were more prevalent among black women aged 20-29 years old, with 4 to 7 years of education, living without a partner, who had 1 to 4 pregnancies; 4 to 6 prenatal appointments, started prenatal care up to the 1st trimester of the pregnancy. The deaths occurred mainly in the postpartum period (up to 42 days). The results showed that maternal mortality is not only a public health problem: it is also a social issue. The knowledge provided by this study may help managers, health workers and the society to develop joint public policies and implement strategies aimed to reduce the number of maternal deaths in the region.